THE REASSONES OF BEING SPENSTER - Suren akram hamanajm (QALAAI ZANIST JOURNAL, 2020)
Unmarried woman is a term referring to an unmarried woman who is older than what is perceived as the prime age range during which women should marry. It could also indicate that a woman is considered unlikely to ever marry. The term originally denoted a woman whose occupation was to spin. This research has two gates, the first gate is dedicated to the theory of the research and it has three chapters. In chapter one, a research problem, a research significance, a research purpose has been written then. In chapter two the concept of (Consequence, spinster, marriage) has been defined as well as chapter three is about the reasons and The Influences of spinster. The second gate has been dedicated for applied research and it has the community of the Research, the example of the Research, the method of the Research, the Areas of the research and Tools for Gathering Information. Finally the Conclusion, Research results, Research recommendations Research suggestions, Bibliography, Appendix. Has been written.